Oi, meus amores! O cotidiano em narrativas femininas no youtube - Rocha, Camila Fregona (2020)
This study aims to analyze female YouTube channels that use the platform to present narratives about their daily routines. Therefore, lunch preparation, going to the market, house organization ideas and exposing the intimacies of the content creators’ private lives are presented on their channels - which gather a large number of views. Thereon, the objective of this research is to understand whatever attracts people's attention towards channels with everyday content, as well as to investigate which communicational processes enable the success of such narratives on YouTube. Hence, the corpus of this study is formed by the YouTube channels called ´Clarear´ and ´Jéssica Barbosa´, which are led by two Brazilian youtubers who show their daily routines on the platform. Therefore, it´s an exploratory research that bases its methodology on ethnography and content analysis. This study is divided into three chapters: the first one is a bibliography review about cultural studies - that brings this particular kind of approach closer to the concept of cyberculture; the second one investigates the dynamics on YouTube and the territorialities built in this online territory where the research is focuded on; the third and final one details all the methodological procedures and presents the investigation of the corpus itself, with an in-depth study about `Clarear´, including the analysis of three videos published by Rúbia, together with comments made by the audience on its respective content. The results showed that the youtubers usually publish their videos based on four main themes: Home, Cooking, Routines and Private Life. Together, they represent the exposure of a mediatized daily life, which entails content production routines with video planning, choice of appealing video titles in order to draw people´s attention, series-format themes and space-time asynchrony between the production and the releasing of content. The house is an important territory for the construction of these women's narratives, which conveys the reproduction of social markers related to the female sign, such as domestic economy. These channels audience – mostly female – may find aspects in the videos upon which they can recognize themselves and relate to, what generates a sense of belonging and a feeling of intimacy between them and the youtubers, which contributes to their will to keep on following these women´s daily routines.